The rhetoric of accountability in Gloria Macapagal Arroyo's State of the Nation Addresses (2001-2005) - Navera, Gene S. (2006)
A constitutionally mandated speech, the State of the Nation address regarded as one of the most important public addresses every year. Delivered by no less than the President of the Republic, the SONA presents the head of state's analysis of the national situation, serves as a means through which the government demonstrates its accountability to the people, and privileges the executive to recommend to Congress what the former perceives as fitting response to national exigencies. The fact that the SONA provides accounting for presidential actions and decisions can be interpreted, though, as a face-saving or image-restoring act. The SONA can be used as an instrument to restore the image of a perennially challenged presidency. This study examines the State of the Nation addresses of President Gloria Macapagal Arroyo from 2001-2005. Using tools and methods of the rhetorical criticism, it analyzes how these speeches have been used to account for the major decisions and actions made by the Arroyo administration during its first four years in power: Seen as interrelated discourses, the speeches reflect the Arroyo administration's rhetorical construction of reality: a curious casting and recasting of the presidential persona and the reconstitution of the Filipino people as receiving ends of democratic processes, and a persistent effort to glorify the incumbent administration. This paper argues that the SONA can actually be regarded as an agency that privileges political and personal interests.